Comparative neurotoxicity of dietary methylmercury and waterborne inorganic mercury in fish: evidence of optic tectum vulnerability through morphometric and histopathological assessments - Carvalho, Patrícia S. (2023)
This work investigated the effects of inorganic mercury (iHg) and methylmercury (MeHg) on the fish optic tectum morphology, viz. in relation to: i) vulnerability of specific optic tectum layers; ii) preferential targeting of Hg forms to neurons or glial cells; iii) comparative toxicity of iHg and MeHg in this brain area that is in the maintenance of several fish behaviors. Two experiments exposing juvenile white seabream (Diplodus sargus) to waterborne iHg [HgCl2 (2 μg L−1)] and dietary MeHg (8.7 μg g−1) were performed, comprising both exposure (7 and 14 days; E7 and E14, respectively) and post-exposure (28 days; PE28) periods. Morphometric assessments were performed using stereological methods where the layers of the optic tectum were outlined, while its area and the number of neurons and glial cells were estimated. A histopathological assessment was also performed per section and per layer of optic tectum. iHg exposure did not trigger the loss of neurons during the exposure periods, while a decrease of glial cells was detected in a single layer of the optic tectum at E14. Differently, upon MeHg exposure, a decrease on the number of neurons and glial cells was found in several layers of optic tectum. In the post-exposure, both Hg forms triggered the loss of neurons, while only MeHg exposure led to a decrease on the number of glia cells. The histopathological assessment pointed out a higher toxicity of MeHg in the optic tectum layers, particularly in the post-exposure period, while no significant alterations were found in fish exposed to iHg. Hg forms targeted preferentially neurons. iHg and MeHg are relevant neurotoxicants to fish, with MeHg exposure leading to a higher toxicity than iHg in the optic tectum. After 28 days of post-exposure, iHg and MeHg neurotoxicity remained prominent, suggesting long-term effects of these toxicants.